2016
DOI: 10.1186/s40101-016-0088-4
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potential and postural muscle activity during standing on an oscillating table while the knee, hip, and trunk are fixed

Abstract: BackgroundIn this study, a cast brace was used to immobilize the knee, hip, and trunk, and relations between the event-related brain potential (ERP) and postural muscle activity were investigated while standing on an oscillating table.MethodsTwelve healthy young adults maintained a standing posture for 1 min per trial while oscillating in the anteroposterior direction at 0.5 Hz with a 2.5-cm amplitude. Trials were performed without and with the cast brace (no-fixation and fixation condition, respectively) unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Of note, since the ankle angle decreases during the period where the PAR occurred (and the TA shortens accordingly), that burst might include the so-called “shortening reaction” (Katz and Rondot, 1978 ; Bathien et al, 1981 ; Berardelli and Hallett, 1984 ), the amplitude of which is known to depend on the central set (Miscio et al, 2001 ). This would be in keeping with the notion that, during adaptation, PAR can be modulated at cortical level, since the cortex is certainly involved in controlling critical postures (Taube et al, 2006 ; Maki and McIlroy, 2007 ; Nardone et al, 2008 ; Petersen et al, 2009 ; Tokuno et al, 2009 ; Bolton et al, 2011 ; Zwergal et al, 2012 ; Obata et al, 2014 ; Fujiwara et al, 2016 ). It has been recently suggested that the motor cortex confers sophisticated feedback to these responses, thereby potentially participating in their calibration (Pruszynski et al, 2011 ; Pruszynski and Scott, 2012 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Of note, since the ankle angle decreases during the period where the PAR occurred (and the TA shortens accordingly), that burst might include the so-called “shortening reaction” (Katz and Rondot, 1978 ; Bathien et al, 1981 ; Berardelli and Hallett, 1984 ), the amplitude of which is known to depend on the central set (Miscio et al, 2001 ). This would be in keeping with the notion that, during adaptation, PAR can be modulated at cortical level, since the cortex is certainly involved in controlling critical postures (Taube et al, 2006 ; Maki and McIlroy, 2007 ; Nardone et al, 2008 ; Petersen et al, 2009 ; Tokuno et al, 2009 ; Bolton et al, 2011 ; Zwergal et al, 2012 ; Obata et al, 2014 ; Fujiwara et al, 2016 ). It has been recently suggested that the motor cortex confers sophisticated feedback to these responses, thereby potentially participating in their calibration (Pruszynski et al, 2011 ; Pruszynski and Scott, 2012 ).…”
Section: Discussionsupporting
confidence: 66%
“…Fujiwara et al ( 2007 ) described adaptation of the balancing strategy to continuous floor oscillation. By recording event-related potentials, reflecting cortical activation by sensory information related to the postural disturbance, they suggested that attention to information processing decreases with adaptation (Fujiwara et al, 2012 , 2016 ). Mierau et al ( 2015 ) also reported adaptation of the negative cortical potential and reduced muscle co-contraction during a prolonged balancing task under critical standing-balance condition.…”
Section: Introductionmentioning
confidence: 99%